1996
DOI: 10.1016/s0035-9203(96)90437-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged clearance of microfilaraemia in patients with bancroftian filariasis after multiple high doses of ivermectin or diethylcarbamazine

Abstract: In a double-blind trial on 37 asymptomatic microfilaraemic subjects (minimum 400 microfilariae [mf] per mL) with Wuchereria bancrofti infection, the safety, tolerability and macrofilaricidal efficacy of 12 fortnightly doses of ivermectin, 400 micrograms/kg (ivermectin group), was compared with 12 fortnightly doses of diethylcarbamazine (DEC), 10 mg/kg (DEC group), over a period of 129 weeks after treatment. A control group (LDIC group) was treated with low dose ivermectin to clear microfilaraemia, for ethical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Previous studies have shown that filarial antigen levels decrease by ∼ 50% after single-dose DEC treatment, 18,25,26 and a 61% decrease was observed in the present study. Previous studies have also reported that filarial antigen tests usually remain positive after single-dose DEC treatment, and this was also true for the majority of subjects in the present study, including some who completely cleared MF after treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that filarial antigen levels decrease by ∼ 50% after single-dose DEC treatment, 18,25,26 and a 61% decrease was observed in the present study. Previous studies have also reported that filarial antigen tests usually remain positive after single-dose DEC treatment, and this was also true for the majority of subjects in the present study, including some who completely cleared MF after treatment.…”
Section: Discussionsupporting
confidence: 75%
“…lymphatic filariasis, onchocerciasis, loaisis, ascariasis, trichuriasis, hookworm and lice), in more than 20 clinical trials in ten countries, including India [42], Cameroon [23], Ghana [43], Gabon [44], Sri Lanka [4547], Mali [48], Papua New Guinea [49, 50], French Polynesia [51–58], Brazil [5962], Haiti [63, 64], and France [65]. Repeated ivermectin administration at doses of 400 µg/kg was safe in two trials in adults who were treated every two weeks for 12 weeks in Sri Lanka [45] and Brazil [61]. The ivermectin dose of 400 µg/kg was deemed safe enough to perform several rounds of MDA to thousands of people in India [42], Cameroon [23], Papua New Guinea [49], and French Polynesia [56, 57] with minimal adverse events reported.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against larval infection is possible, as dose-dependent responses have been demonstrated using killed and irradiated microfilarial and larval vaccines of several filarial worm species, and abbreviated larval infections with D. immitis [67, 90, 92, 108], O. volvulus [109], Loa loa [110], B. malayi [71, 111] and W. bancrofti [112]. Additionally, concurrent administration of the immunostimulant Freund’s complete adjuvant (FCA) with an abbreviated larval infection elicited a stronger protective immune response than an abbreviated infection without FCA, or an irradiated infection alone [92].…”
Section: Administration To Filarial Wormsmentioning
confidence: 99%
“…However, repeated doses at sufficient intervals with either live or killed vaccines elicit a memory response, which results in a higher antibody titer and more effective immune protection [93, 109, 110, 112]. …”
Section: Administration To Filarial Wormsmentioning
confidence: 99%